2020
DOI: 10.1371/journal.pone.0231410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peer tutoring on middle school students’ mathematics self-concepts

Abstract: The effects of peer tutoring on students' mathematics self-concepts were examined. The Marsh questionnaire was used to measure students' mathematics self-concepts before and after implementation of a peer tutoring program. A pretest posttest control group design was employed. Study participants included 376 students from grades 7 to 9 (12 to 15 years old). No statistically significant differences were reported between the pretest and the posttest for any of the control groups. Statistically significant improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 110 publications
2
28
0
1
Order By: Relevance
“…Previous studies in the field state that, from a psychological perspective, reciprocal tutoring is better than fixed tutoring (Miravet et al, 2014). Mathematics self-concept and mathematics attitude seem to benefit more from the role exchange that takes place during reciprocal tutoring (Cheng & Ku, 2009;Fantuzzo et al, 1989;Moliner & Alegre, 2020;Sutherland & Snyder, 2007). No previous literature reviews or meta-analysis have shown significant differences between both types in the academic achievement variables (Leung, 2015(Leung, , 2019b.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Previous studies in the field state that, from a psychological perspective, reciprocal tutoring is better than fixed tutoring (Miravet et al, 2014). Mathematics self-concept and mathematics attitude seem to benefit more from the role exchange that takes place during reciprocal tutoring (Cheng & Ku, 2009;Fantuzzo et al, 1989;Moliner & Alegre, 2020;Sutherland & Snyder, 2007). No previous literature reviews or meta-analysis have shown significant differences between both types in the academic achievement variables (Leung, 2015(Leung, , 2019b.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…The confirmation of hypothesis 2 (posttest scores for the experimental group in both, mathematics learning anxiety and mathematics evaluation anxiety will be significantly lower than the posttest scores for the control group) was predictable taking into account the findings of recent studies in the field of peer tutoring and mathematics (Campbell, 2019;Grove et al, 2019;Moliner and Alegre, 2020;Yoo, 2020). In them, it is reported how the experimental group outscores the control group and statistically significantly differences are found when analyzing other psychological variables such as mathematics self-concepts or mathematics attitude.…”
Section: Discussionmentioning
confidence: 71%
“…Afterward, the students participated in the reciprocal peer tutoring sessions for approximately 20 min to check and finalize the work they had done individually. Indications and protocols analogous to those provided by Moliner and Alegre (2020) were followed during peer tutoring. Working in pairs, students had to compare the results they had arrived at when working on their own, share the procedures they had employed to solve the tasks, ask each other questions regarding the exercises and problems, and work together to solve any problems that they hadn’t completed when working independently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, students perceived that the peer tutoring program provided them with opportunities that were not otherwise available within the curriculum [19,20]. The main conclusion of this study is that reciprocal and peer tutoring can be very beneficial [21].…”
Section: Research Articlementioning
confidence: 78%